Clean energy solutions for rural development in Ethiopia: Combining forces across key energy actors - Ringler, Claudia (CGIAR, 2024)
Initiative Co-lead Claudia Ringler spoke with three NEXUS Gains partners in Ethiopia to understand more about their work to expand rural energy development in an inclusive and sustainable way, and how NEXUS Gains supports them to achieve this.